An Exploratory Study of Funding for Agricultural Communications Offices - Larry R. Whiting (Journal of Applied Communications, 1984)
The Department of Information and Publications at the University of Maryland serves the Maryland Cooperative Extension Service, the Maryland Agricultural Experiment Station, and the College of Agriculture.